Transition of the adolescent patient to the adult clinic - (:unkn) unknown (Multimed Inc., 2009)
Transition is the purposeful, planned movement of adolescents and young adults with chronic and medical conditions from child-centered to adult-oriented health care systems. For patients with chronic diseases that have begun early in life and continued into adulthood, transition is a very important period requiring not only medical, but also psychological and social support, which should begin on the day of diagnosis. Lack of coordination between pediatric and adult units, resistance of the adolescents and their families, and lack of planning and institutional support are a few of the numerous hardships that are encountered while trying to sustain a successful transition. This article reviews the steps of transition and also solutions for the potential barriers to a successful transition. Copyright © 2009 International Society for Peritoneal Dialysis.
Keywords: Adolescents; Adult care; Children; Chronic disease; Transition